Analysis of public attitudes and perceptions towards renewable energy sources in Montenegro. (November 2020) - Djurisic, Vladimir; Smolovic, Julija Cerovic; Misnic, Nikola; Rogic, Suncica
Abstract: The main objective of this research is to identify the attitudes and public perceptions towards the renewable energy sources (RES) in Montenegro. In this paper, the underlying motive for the research is reflected through the importance of the renewable energy sources related topic and its role in the sole process of the energy market transformation. This study was especially inspired by the fact that no similar research has ever been conducted in this domain. The questionnaire designed for the purpose of the survey was conducted in the period from November 2019 to January 2020, with a sample of 1012 respondents from every region in Montenegro. Application of the Structural Equation Model (SEM) was intended to examine the cause-and-effect relationships between defined constructs in order to determine what is influencing the consumers' perceptions and behaviours towards RES. The obtained results show that, with other conditions remaining the same, the construct of perception towards RES determines behaviour the most, with the level of 32.8%, while the awareness construct takes second place in explaining the behaviour towards RES, with the percentage of 20.7. Finally, the intended special contribution of this research is in recognizing the gap between attitudes and perceptions on one hand, and actual behaviour on the other, after it was recognized as a barrier to greater implementation of RES in the Montenegrin energy market.